Penggunaan Gadget terhadap Kelainan Refraksi pada Siswa-Siswi - Sri Lestari Ramadhani Nasution; Friska SR; Ermi Girsang; Mangatas Silaen (Journal of Telenursing (JOTING), 2022)
This study aims to identify the effect of using gadgets on refractive errors. The method used is cross-sectional. The results showed that there was no effect on the duration of using the gadget, the intensity of light, the position of using the gadget on refractive errors, but there was an effect of visibility and genetics on refractive errors. In conclusion, visibility and genetics are factors that affect refraction. Keywords: Gadgets, Refractive Disorders, Myopia